Deficiencies of Chromatophore Proteins in Some Mutants of Rhodopseudomonas spheroides with Altered Carotenoids - Segen, Barbara J. (1971)
Chromatophore proteins of a wild type and three mutant strains of Rhodopseudomonas spheroides were examined by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. The mutants consisted of a green and a blue-green one, whose phenotypes were essentially the same as those of known mutants, and a brown one, which may be a double mutant and represents a new phenotype. Wild-type chromatophores contained at least six major and seven minor protein bands, with molecular weights ranging from 10,000 to 65,000. The green mutant contained the same protein bands in the same relative quantities. The brown mutant had one protein completely missing and no other alterations. The blue-green mutant was deficient in a different protein, and had reduced quantities of all proteins with molecular weights less than 25,000. Chromatophores were separated into a fraction containing the reaction centers and a fraction containing the light-harvesting bacteriochlorophyll by treatment with sodium dodecyl sulfate. Eight of the proteins were found only in the reaction center fraction, one was only in the light-harvesting fraction, and the remainder were present in both fractions. The protein missing from the brown mutant was found to be a component of the reaction center fraction, whereas the proteins which were missing from the blue-green mutant were all components of the light-harvesting fraction. Some implications for the structure and biogenesis of chromatophores are discussed.